2020
DOI: 10.5530/jyp.2020.12.15
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Community Pharmacists towards Adverse Drug Reactions Reporting

Abstract: Background: Spontaneous reporting systems (SRSs) play an important role in identifying adverse drug reactions. In most of the developed countries, community pharmacists contribute to the pharmacovigilance system to a greater deal. Objectives: Present investigation is designed to evaluate the impact of clinical pharmacists' educational intervention on ADRs and pharmacovigilance program of India (PvPI) among community pharmacists in Anantapur district, Andhra Pradesh, India. Methods: It was a single group, pre-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…The study found that community pharmacists’ knowledge and attitudes toward diabetes care and management improved significantly following the educational session. Similar outcomes have been reported in Croatia and India, where the clinical expertise of community pharmacists increased following an interactive clinical pharmacy workshop [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 75%
“…The study found that community pharmacists’ knowledge and attitudes toward diabetes care and management improved significantly following the educational session. Similar outcomes have been reported in Croatia and India, where the clinical expertise of community pharmacists increased following an interactive clinical pharmacy workshop [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 75%
“…This finding is similar to that of other studies on the same topic in developing countries, demonstrating that this area still requires improvement. [4][5][6]8,19 No significant statistical differences were found in the results of the total KAP score among health professionals, However, some particular groups stood out, which could be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Incentive payment schemes, legally-required reporting or use of reporting as a quality indicator in the GPs' contracts have been suggested so as to improve ADR reporting rates (114), however, none of them have succeeded to do so in many countries (43). Several studies suggest active training and educational interventions for HCPs on pharmacovigilance may improve their attitude and knowledge of ADR identification and reporting (115)(116)(117). Pharmacists are wellpositioned to identify and report ADRs (43, 118-120) and the quality of ADR reports submitted by both community and hospital pharmacists have been found to be comparable to reports from hospital doctors (121)(122)(123)(124).…”
Section: Figure 3 Endocrine System A) Antidiabetic Drugs (Biguanides ...mentioning
confidence: 99%